Priorytety duszpasterskie w Diecezji Wrocławskiej w pierwszych latach pasterskiej posługi biskupa Adolfa Bertrama (1) - Michał Piela (Wrocławski Przegląd Teologiczny)
The period of World War I, which also marked the beginnings of Bertram’s reign over the diocese of Wrocław, was very difficult. It was the time of war, the collapse of the German Empire and the rise of the Weimar Republic. On the basis of the preserved protocol from the Conference of the Deans of 1915, the author has made an attempt to investigate certain pastoral issues to which bishop Bertram and his colleagues paid particular attention. The subjects which were of great interest to the ordinary and the deans in 1915 included: the spread of Christian and catechism teachings by the priests on Sunday afternoons, teaching religion in school, access to Holy communion at a young age and its regular administration in the last years of schooling, pastoral care over seasonal workers, Catholic oversight over young people and youth groups, the St. Boniface association in the diocese, St. Hedwig charity, folkloric missions, and the fight with alcoholism. The next reflection will contain the subjects discussed at the next conference of the Deans in 1918.